2008
DOI: 10.1038/cgt.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

The ERBB3 receptor in cancer and cancer gene therapy

Abstract: ERBB3, a member of the epidermal growth factor receptor (EGFR) family, is unique in that its tyrosine kinase domain is functionally defective. It is activated by neuregulins, by other ERBB and nonERBB receptors as well as by other kinases, and by novel mechanisms. Downstream it interacts prominently with the phosphoinositol 3-kinase/AKT survival/mitogenic pathway, but also with GRB, SHC, SRC, ABL, rasGAP, SYK and the transcription regulator EBP1. There are likely important but poorly understood roles for nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(173 citation statements)
references
References 397 publications
(510 reference statements)
3
170
0
Order By: Relevance
“…41 It also suppresses ErbB3 when EBP1 binds to it. 42 ErbB3 is an epidermal growth factor receptor (EGFR), and is activated by various growth signals and other EGFR family proteins such as ErbB2. The interactions between EBP1 and ErbB3 are disrupted by the ErbB ligand, heregulin, causing nuclear translocation of EBP1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 It also suppresses ErbB3 when EBP1 binds to it. 42 ErbB3 is an epidermal growth factor receptor (EGFR), and is activated by various growth signals and other EGFR family proteins such as ErbB2. The interactions between EBP1 and ErbB3 are disrupted by the ErbB ligand, heregulin, causing nuclear translocation of EBP1.…”
Section: Resultsmentioning
confidence: 99%
“…44 Interestingly, RSK and MSK are downstream molecules of ErbB2 and ErbB3 signaling pathway, and heregulin causes increased or prolonged signaling through AKT, ERK, RSK, and MSK cascades. 39 , 42 RSK and MSK were phosphorylated by tRNA Leu overexpression, without growth stimuli such as serum or amino acids. We therefore hypothesized that free tRNA Leu could induce the disruption of the interaction between EBP1 and ErbB3, leading to the inactivation of ErbB3 and/or ErbB2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because the HER3 and HER4 receptors are frequently over-represented in some cancers, [52][53][54] an Ad with HRG-mediated expanded tropism may have potential therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an HRG-targeted virus may be valuable for the treatment of a number of human malignancies, including breast and ovarian carcinomas, in which members of HER receptor family are frequently overexpressed. [50][51][52][53][54] In this regard, Han and co-workers 55 have demonstrated that a recombinant Moloney murine leukemia virus carrying a gp70-HRG fusion envelope protein was able to infect normally refractory human breast cancer cell lines in a receptor-dependent manner.…”
Section: Introductionmentioning
confidence: 99%